Integrated course on ocular anatomy for ophthalmology clerkship - Li Huang; Xinyu Liu; Yuxian Zou; Xianchai Lin; Zhen Mao (BMC Medical Education)
Abstract Background Obtaining a full understanding of the anatomical structure of the eyeball and the contents within the eye plays a crucial role in learning eye diseases. However, it can be challenging for beginners to quickly learn, memorize, and apply this anatomical knowledge. To improve the teaching of ocular anatomy and help students overcome learning difficulties in ophthalmology clerkship, Zhongshan Ophthalmic Center developed an integrated ocular anatomy course comprising three main components: 'online preview,' 'lecture,' and 'wetlab dissection'. Methods Fifty-five fourth-year medical students from Sun Yat-sen University were recruited for this study. The impact of the integrated course was evaluated through three in-class quizzes (T1: pre-teaching assessment, T2: post-wetlab training, and T3: end of clerkship) and assessments of students' self-confidence levels. Additionally, students' course evaluations were gathered via a questionnaire survey. Statistical analyses were conducted via ANOVA and the Kruskal–Wallis test. Results The integration course significantly improved the mean scores of post-teaching tests (67.08 ± 10.27 vs. 74.36 ± 12.75 vs. 78.81 ± 12.70, P < 0.0001) and the students’ self-confidence scores (P < 0.0001). Fifty-four participants were satisfied with the integrated anatomy course (79.3% strongly agreed, 18.2% more agreed). Fifty-two participants agreed (76.4% strongly agreed, 18.2% more agreed) that the course could help them better understand the anatomy of the eye. Conclusions This integrated ocular anatomy course can aid students in better understanding and retaining the anatomy and function of ocular structures, serving as a valuable adjunct teaching strategy that can be further applied to ophthalmology clerkship.